Tutela penal ambiental e princípios penais - Rodrigues, Carlos Eduardo Afonso (2012)
The purpose of this essay is to reinforce the principle of the minimal intervention of the Criminal Law, placing it as a head principle of the modern environmental crimination and setting it as the last resort, due to its austerity and the selectivity of its penalties and of its stigmatizing character, on the battle against the unbridled consumption of the natural resources which currently occurs. Previously to the concretion of a political-criminal view of the environmental crimination, the legislative instruments used in the environmental protection were subject of a rigorous legitimacy check, finding that, from the analysis of the criminal elements in the Constitution, various are the legal-dogmatic implications that convey and the jeopardy to freedom is great, leading to serious hesitation about the aptitude of the Criminal Law to refrain harmful acts to the environment. The modest contribution that the criminal regulation can offer to the environmental protection, mainly due to the fact that it s a systemic-structural issue demanding broader solutions than the exceptional incidence of the Criminal Law, on one side, and the existence of other mechanisms formal and informal oriented to the effective protection of the environment, on the other side, bind the assumption of measures outside of the Criminal Law that aim to confront the growing environmental degradation, materializing at the same time a serious decriminalizing scheme of the criminal dispositions pertaining Criminal Environmental Law existing today